EVALUASI REPRODUKSI INDUK KELINCI NEW ZEALAND PADA BERBAGAI PARITAS (Studi Kasus di UD. Alastika Jaya Desa Tulungrejo Kecamatan Gandusari Kabupaten Blitar) - Iva Mardiani Fatimah; Nita Opi ari kustanti; Edya Moelia Moeis (AVES: Jurnal Ilmu Peternakan, 2019)
The aim of this study is to find out reproctive performance of New Zealand doe in UD. Alastika Jaya. This study use 35 of 51 doe population as the sample and field survey to take primary and secondary data from observation and interview as the research method. The result of observation and data analysis of study indicate that average value of service per conception (S/C), long of days open, gap of bred after whelped, interval of birth, litter size at birth, and litter size at weaning in a row is 2,17+0,57, 33,33+16,56 days, 32,6+22,14 days, 65,67+16,54 days, 6,65+2,54 kits, dan 4,24+2,05 kits